Concept of Primitive Beliefs in the Neolithic (Journal of Misan Researches, 2024)
The Neolithic is considered an important stage in human life, in which he learned agriculture, animal domestication, and stability, which had a great impact in creating spiritual, sensory images, which brought him to a stage of contemplation and innate belief in certain beliefs, especially in the beginnings of the Neolithic, which helped him communicate with What surrounds him, from a cosmic, environmental and social environment, with innate answers to questions and fears that occupied his mind, so that these innate beliefs become a primitive stage for the tendency of faith, sanctification and worship, in the advanced civilizational periods of human life.